Green sonochemistry assisted synthesis of hollow magnetic and photoluminescent MgFe2O4–carbon dot nanocomposite as a sensor for toxic Ni(ii), Cd(ii) and Hg(ii) ions and bacteria. Issue 37 (28th June 2021) - Ahmadian-Fard-Fini, Shahla; Ghanbari, Davood; Amiri, Omid; Salavati-Niasari, Masoud
Abstract : The purpose of this study is synthesis of magnetic and photoluminescence nanoparticles at the same time for finding of bacteria that could be fatal and its detection are crucial for some illness prohibition. Abstract : The purpose of this study was synthesis of photoluminescent nanoparticles for detection of toxic metal ions. Also, these controllable magnetic nanocomposites were used for detection of Pseudomonas aeruginosa bacteria. Carbon nano-templates were formed by calcination and sonication of lemon extract as a bio-compatible precursor. Then MgFe2 O4 nanoparticles were incorporated on the carbon nano-templates. The composite was calcinated to decompose carbon and obtain hollow structures. Finally, photoluminescent carbon dots were deposited on the porous magnesium ferrite core. Because of the hollow structure, carbon dots can diffuse to the Mg-ferrite core so magnetic and photoluminescence properties are available simultaneously. Photoluminescence intensity decreases with increasing Ni(ii ), Cd(ii ), Hg(ii ) metal ions and Pseudomonas aeruginosa . Results show an effective nanostructure for identification of toxic metal ions and also bacteria.